1996
DOI: 10.1002/(sici)1097-0290(19960305)49:5<512::aid-bit4>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of operating conditions for protein purification using expanded bed techniques: The effect of the degree of bed expansion on adsorption performance

Abstract: A strategy for the optimization of an expanded bed adsorption process has been developed by studying a model system involving the adsorption of lysozyme onto the adsorbent STREAMLINE SP. The hydrodynamic and adsorption properties of this ion exchange adsorbent in a variety of viscosities of feedstocks have been compared by analyzing bed expansion characteristics, liquid phase dispersion characteristics, equilibrium adsorption isotherms, and mass transfer characteristics. Additionally, the influences of the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 15 publications
10
47
1
Order By: Relevance
“…The decrease of the protein adsorption was observed on the increase of the protein content in the medium. Chang and Chase [9] and Tong et al [11] described a similar kinetic adsorption behavior for lysozyme in Streamline DEAE resin and BSA in Streamline SP resin, respectively. The reduction in the protein adsorption could be attributed to the elevation of the solution viscosity.…”
Section: Kinetic Of Adsorptionmentioning
confidence: 83%
See 1 more Smart Citation
“…The decrease of the protein adsorption was observed on the increase of the protein content in the medium. Chang and Chase [9] and Tong et al [11] described a similar kinetic adsorption behavior for lysozyme in Streamline DEAE resin and BSA in Streamline SP resin, respectively. The reduction in the protein adsorption could be attributed to the elevation of the solution viscosity.…”
Section: Kinetic Of Adsorptionmentioning
confidence: 83%
“…Adsorption chromatography in batch mode, also called batch adsorption, is a simple process applied to obtain (i) equilibrium and kinetic data of adsorption and desorption processes [9][10][11][12] and (ii) model parameters to be used in the simulation of chromatography process scale-up, such as expanded bed and simulated moving bed techniques. It can be cited, for example, in the intra-particle diffusivity parameter [13].…”
Section: Introductionmentioning
confidence: 99%
“…An early breakthrough was recorded as the linear superficial velocity was increased from 0.5 to 5 cm/min. Chang and Chase [20], and Chase [28] also reported that the shape of breakthrough curves varied with superficial velocity when adsorption kinetics were slow relative to the mass transfer rate. A slower superficial velocity during feedstock loading in a packed bed operation may have assisted in giving more interaction time for proteins and adsorbents, thus led to a higher binding of N protein onto the adsorbent as shown by the results tabulated in Table 3.…”
Section: Effect Of Superficial Velocity On the Breakthrough Curvementioning
confidence: 95%
“…Recovery throughput is another parameter in affinity purification. This refers to the amount of adsorbed protein at 10% breakthrough divided by the volume of adsorbent and the processing time; both were calculated according to Chang and Chase [20]. The time for protein adsorption was recorded once the 10% breakthrough was reached.…”
Section: Breakthrough Curve and Dynamic Binding Capacitymentioning
confidence: 99%
“…This method reduces the amount of protein pretreatment required, and makes the capture of target proteins from cell homogenate feedstock possible [21][22][23], thus achieving a higher product recovery in a shorter time. In the first step, phycocyanins were recovered by the adsorbent while the cell debris, particulates and contaminants in the extract pass through with the upward flow.…”
Section: Introductionmentioning
confidence: 99%